2017
DOI: 10.1016/j.rboe.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Hip disarticulation – case series analysis and literature review

Abstract: ObjectiveTo present a retrospective study of 16 patients submitted to hip disarticulation.MethodsDuring the period of 16 years, 16 patients who underwent hip disarticulation were identified. All of them were studied based on clinical records regarding the gender, age at surgery, disarticulation cause, postoperative complications, mortality rates and functional status after hip disarticulation.ResultsHip disarticulation was performed electively in most cases and urgently in only three cases. The indications had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…Patients with vascular disease have high rates of wound complications, which often preclude the eventual fitting of the prosthesis. 4) The aforementioned findings imply that the success of prothesis fitting may be dependent on the type of underlying disease. Given that the primary disease in our case was a malignant tumor, for which wound complications are uncommon, the situation was favorable for the early initiation of prosthesis fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with vascular disease have high rates of wound complications, which often preclude the eventual fitting of the prosthesis. 4) The aforementioned findings imply that the success of prothesis fitting may be dependent on the type of underlying disease. Given that the primary disease in our case was a malignant tumor, for which wound complications are uncommon, the situation was favorable for the early initiation of prosthesis fitting.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent case study found mortality was higher in disarticulations with trauma (66.7%) versus tumorous (60%) diagnoses. 9 Similarly, the risk of postoperative infection, flap necrosis and wound dehiscence increases with emergency operation. Other known risk factors include peripheral vascular disease and previous above-knee amputation.…”
Section: Discussionmentioning
confidence: 99%
“… 2 A recent case study found mortality was higher in disarticulations with trauma (66.7%) versus tumorous (60%) diagnoses. 9 …”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the cause of rejection of the prosthesis was attributed to the difficulty of ambulation, intolerance to the socket, or excessive weight of the prosthesis7 ) . For HDAs including elderly people to acquire the ability to walk in the community, it is generally considered necessary for them to have few comorbidities, an adequate degree of physical fitness, and individual motivation2, 3, 9, 10, 14 ) . In the present case, it was confirmed that the physical function was sufficient before fitting the prosthesis, the control of rheumatoid arthritis was comparatively good, and the motivation for reacquiring walking was very high.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that the proportion of HDAs who attain gait function still remains low14 ) ; however, depending on the condition and type of comorbidity, a prosthetic limb can be used in the rehabilitation of HDAs in the consideration of the physical and psychological state of the patient. The present case highlights the fact that even HDAs with comorbidities can use prosthetic limbs to achieve clear goals.…”
Section: Discussionmentioning
confidence: 99%